2007
DOI: 10.5194/angeo-25-27-2007
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Rayleigh and sodium lidar temperature climatologies

Abstract: Abstract.Temperature measurements from the PCL Rayleigh lidar located near London, Canada, taken during the 11 year period from 1994 to 2004 are used to form a temperature climatology of the middle atmosphere. A unique feature of the PCL temperature climatology is that it extends from 35 to 95 km allowing comparison with other Rayleigh lidar climatologies (which typically extend up to about 85 km), as well as with climatologies derived from sodium lidar measurements which extend from 83 to 108 km. The derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 21 publications
(24 reference statements)
2
35
0
Order By: Relevance
“…In order to extend our results to include an extra 10 km on top, the inversion method is used to perform temperature climatology for the PCL High Level Rayleigh channel. In this study, the Argall and Sica methodology was followed to form the temperature climatologies where the methodology is explained in detail in Argall and Sica (2007 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to extend our results to include an extra 10 km on top, the inversion method is used to perform temperature climatology for the PCL High Level Rayleigh channel. In this study, the Argall and Sica methodology was followed to form the temperature climatologies where the methodology is explained in detail in Argall and Sica (2007 …”
Section: Methodsmentioning
confidence: 99%
“…Temperature retrievals from Rayleigh-scattering lidar measurements have been performed using the methods by Hauchecorne and Chanin (1980; henceforth HC) and Khanna et al (2012). Argall and Sica (2007) Khanna et al (2012) used the inversion technique to retrieve atmospheric temperature profiles and found that it had advantages over the HC method. This paper presents an extension of the PCL climatologies created by Argall and Sica (2007) and Iserhienrhien et al (2013).…”
Section: Rayleigh and Raman Scatter Measurements Frommentioning
confidence: 99%
See 1 more Smart Citation
“…In Argall and Sica [4], RS temperatures were found to be 7 K cooler than Na temperatures in the altitude range of 80-95 km. Leblanc et al [5], found RS temperatures, from 82-88 km, to be 8-14 K colder than the Na temperatures from 80-82 km and 2-6 K colder from 82-88 km.…”
Section: Introductionmentioning
confidence: 99%
“…Two climatological studies have compared results from the RS and Na lidar techniques using composite year averages from lidar sites spread around the globe, over different observational periods [4,5]. In Argall and Sica [4], RS temperatures were found to be 7 K cooler than Na temperatures in the altitude range of 80-95 km.…”
Section: Introductionmentioning
confidence: 99%